A new species of amphipod of the genus Parhyale Stebbing, 1897 from Chilika Lagoon, India - Patro, Shesdev; Bhoi, Gitanjali; Myers, Alan A.; Sahu, Suchismita (Zootaxa, 2024)
A new species of the genus Parhyale, Stebbing 1897 was collected from the intertidal region of Chilika Lagoon associated with the seaweed Gracilaria sp. Parhyale odian sp. nov. differs from other species of the genus by having a stout robust seta on the surface of the propodus near to dactyl hinge of male gnathopod 1. With the new description of P. odian sp. nov., the global species number in the genus rises to 16.